Haematological effect of iron supplementation in breast fed term low birth weight infants. Issue 1 (21st December 2004) - Aggarwal, D; Sachdev, H P S; Nagpal, J; Singh, T; Mallika, V
Abstract : Aims: To determine the haematological effects of iron supplementation in predominantly breast fed term low birth weight (LBW) infants. Methods: Seventy three healthy term LBW (<2500 g), predominantly breast fed infants aged 50–80 days were randomised into two groups to receive either iron (3 mg/kg/day) (iron supplemented (IS) group; n = 37) or placebo drops (placebo (P) group; n = 36). Haematological parameters and anthropometry were measured at baseline and repeated after four and eight weeks. Results: A total of 62 subjects (32 in the IS group and 30 in the P group) came for the first follow up and 26 (13 in the IS group and 13 in the P group) reported for the second visit. There were no significant differences in serum ferritin and anthropometry. However, covariates (infant age, haemoglobin, and ferritin, and maternal haemoglobin) adjusted haemoglobin change was significantly higher in the IS group after four weeks (4.6 g/l; 95% CI 0.5 to 8.8) and eight weeks (8.6 g/l; 95% CI 1.8 to 15.4). Conclusions: Iron supplementation in a therapeutic dose in term breast fed LBW infants results in a marginal increase in haemoglobin. The functional benefit of this haemoglobin rise requires further evaluation.